Foetal Maceration in Goat- A Case Report - AJITKUMAR, G; KURIAKOSE, ASHA MERINA; GHOSH, K N ARAVINDA; SREEKUMARAN, T (The Indian Journal of Animal Reproduction, 2007)
A case of foetal maceration in a goat is placed on record.